Novel N-doped ZrO2 with enhanced visible-light photocatalytic activity for hydrogen production and degradation of organic dyes. Issue 13 (12th February 2018) - Wang, Yuanyang; Zhang, Yinghua; Lu, Haiqiang; Chen, Yanxin; Liu, Zhenmin; Su, Shen; Xue, Yongbing; Yao, Jianfeng; Zeng, Hongbo
Abstract : Two new types of N-doped ZrO2 photocatalysts ZON and AZON have been synthesized using ethylenediamine as the nitrogen source by a facile and low-cost sol–gel method. Abstract : Two new types of N-doped ZrO2 photocatalysts ZON and AZON have been synthesized using ethylenediamine as the nitrogen source by a facile and low-cost sol–gel method. The N-doped ZrO2 samples have been characterized using various techniques including X-ray diffraction (XRD), UV-Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), photoluminescence spectroscopy (PL) and N2 adsorption–desorption tests. The XRD analysis shows that the crystallinity of ZON samples calcined at 400–600 °C can be indexed to monoclinic ZrO2 ; while the AZON samples calcined at 400–550 °C only show amorphous diffraction patterns. The UV-Vis response of both N-doped ZrO2 samples can be extended to the visible light regime. The high resolution XPS spectra indicate that N element has been doped in the lattice of ZrO2 . Visible-light photocatalytic reactions using the N-doped ZrO2 photocatalysts ( i.e. ZON, AZON) calcined at 450 °C show the highest hydrogen production rate (2.12 mmol g −1 h −1 ) and best methylene orange degradation performance due to substitutional N-doping of the ZrO2 . The novel N-doped ZrO2 materials are demonstrated to be very promising photocatalysts with enhanced visible-light photocatalytic activity. Our results provide useful insights into the development of novel photocatalytic materials for hydrogen production and degradation of organic wastes by narrowing the wide bandgap of semiconductors with high photocatalytic activity under UV-Vis light.